Anthropometry and somatotypes of male soccer players according to their playing positions in a sports school / Faeezad Hasriq Khalid - Khalid, Faeezad Hasriq (2015)
The purpose of the study was to determine the anthropometry and somatotypes of male soccer players according to their playing positions. 64 male soccer players (14.08±0.82 years) were purposively selected in Sekolah Sukan Malaysia Pahang. The following anthropometric variables were measured; weight, height, skinfolds, percentage of body fat and lean body mass. Somatotypes data were calculated using the Somatotype Software Version 1.2.5. Results (mean±SD) were as follow; weight 55.36±9.36kg, height 164.2±7.57cm, BMI 20.41±2.32, skinfolds 59.7±20.76mm, % body fat 14.08±1.19 and lean body mass 47.32±6.70.The mean somatotype of the players was 1.56-3.45-2.74, (endomorph, mesomorph and ectomorph). There were significant difference for players of playing positions in both anthropometry and somatotypes variables (p<0.05) except in endomorphy and mesomorphy (p>0.05). It was concluded that the mean for anthropometry and somatotypes of male soccer players was significant. The inter-positional differences in anthropometry and somatotypes of players mean that a systematic talent identification and selection criterion should be implemented by coaches and team selectors.